(3aWQI GdUGfY aj SeI GdWHGFYs - (3GHf JheQJ , eMeO Hf Ydj Hf JheQJ GdeZQHj GdCfOdSj GdeGdcj, CHh YHO Gddg,J (B391 (3g` s ((3WHfLI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdHQjGJ GdYde YdeGf (B: (3Yde GdCHOGf , hYde GdCOjGf hMO GdWH efbSe Ydi bSejf (B: (3MaX UMI ehLhOI , ChQO UMI eabhOI s
(3BNQgG (B:s
(3NPgG HYde hGdYdje gh GdPi HGdMb CfWbfi hdi hdgG HQi hYdi GdfHi hBdg hUMGHg Udi Edg GdYQT eG HQb SQi s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B312s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs